RESILIENSI PEREMPUAN YANG SEMASA KANAK-KANAK MENJADI KORBAN KDRT - Hani Kumala; Wieka Dyah Partasari (MANASA, 2012)
Violence to women have been going on from time to time. The most common violence that happened is domestic abuse. Not only happen at wife. Domestic violence also happen in children. But some research found that not all the abusive children experience the negative effect. It happens because the differences level of resilience. Grotberg (1995) stated that resilience is the ability to prevent or minimizing the damaging impact of that abusive experience. This research is using qualitative method. The data collection is using interview emthod with general interview guidance to four participant that have characteristic (1) young adulthood women that ages 21-40 (2) has been on domestic violence during their childhood. Two of them are married and two other are single. The result of the research found that the resilience from four subject is affected by the present of social support, intelligence level, temperament and how they appreciated to the resilience factor that they had in their life (I have, I am, I can). The resilience people are theu who had pass the development stages properly. As a kid, they showed the resilience by showing resistance pattern. As a teenager, they will have normal physical. Cognitive, social and emotional development. As a young adulthood, they can forgive abuser and make peace with their past.